Online Dispute Resolution (ODR) As an Alternative Dispute Resolution of The Current Sharia Economics Issues in Indonesia - Karimatul; Adinugraha, Hendri Hermawan; Mayangsari, Putri Ayu (Jurnal Hukum Islam, 2021)
The development of sharia business activities and Islamic Financial Institutions in Indonesia can dispute the parties. Therefore, it is necessary to resolve disputes by current conditions where almost all activities are carried out quickly and efficiently through the help of the internet. This paper analyzes the legality of ODR in Indonesia and ODR from the perspective of sharia economic law. The method used is documentation with a normative juridical approach. The results showed that ODR is an effective method chosen by the parties in resolving sharia economic disputes because it is by current needs which require all activities quickly and easily. ODR also has a clear legal basis through Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. In the perspective of sharia economic law, as long as the principles, objectives, and mechanisms of ODR do not conflict with sharia principles, then ODR is the right choice in resolving disputes on the sharia economy of Indonesia